Surdity in the OR: An Unusual Case of Brainstem Anesthesia - Howard D. Palte; Don P. Hoa; Aldo Pavon Canseco (Case Reports in Anesthesiology)
Brainstem anesthesia is a potentially life-threatening complication of regional ophthalmic anesthesia. This case report chronicles an unusual presentation of brainstem anesthesia following an eye block. The unique features of this case were the presenting symptoms of deafness and slurred speech in the absence of loss of consciousness, respiratory depression, or contralateral ophthalmoplegia. This report underscores two key points: first, the importance of ongoing patient monitoring after performance of an eye block; second, the exigency of supportive therapy in suspected cases of brainstem anesthesia.